Dynamic testing of systems – use of TRNSYS as an approach for parameter identification - Almeida, Patrícia (2015)
Dynamic testing of solar thermal systems is presently defined by ISO 9459-5:2007. The testing methodology is clearly defined in the standard. Presently, laboratories that use Dynamic System Testing methodology only have available for identification of parameters, a closed source program, which is based on a model described by Spirkl and Muschawek (1992). The present paper describes the work done following a different approach for the identification of parameters – use of TRNSYS to simulate the system and use of GENOPT for optimization. Results are presented, both for thermosyphon and forced circulation systems, and show, in most cases, good agreement (differences lower then ±5%) when compared with the results using ISS, v2.7 (from In Situ Scientific Software). Comparison of system energy yield, calculated using TRNSYS for periods higher than one month, with measured energy yield for these periods, was also done for a thermosyphon system showing very good agreement (differences lower than ±3%).